MANAJEMEN PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENTINGNYA REKAM MEDIS DI FASILITAS PELAYANAN KESEHATAN - Anas Rahmad Hidayat; Wahyu Joko Pamungkas (Jurnal Pengabdian Masyarakat Permata Indonesia, 2023)
Medical records have use value as information on health care and patient treatment as evidencein law enforcement processes, fostering medical personnel discipline, enforcing medical ethics, foreducational and research purposes, the basis for health service financing and for compiling healthstatistics. Therefore, the filling of this medical record must be complete and should not be delayedin filling it either for patients or health workers. However, many people do not know the importantfunction of completing medical records and disclosure of personal information that must be givento health care facilities and even health workers who care for them in supporting the quality ofinformation on the medical records. The purpose of this activity is to increase public knowledgeabout the importance of medical records for people seeking treatment at health care facilities. Thematerial presented related to the application of quality in medical records can be carried out startingfrom the preparation of indicators, then the methods used can be in the form of quantitative andqualitative analysis, dimensions depicted in medical record services, namely tangible (physicalevidence), reliability (reliability), responsivness (responsiveness), assurance (assurance) andemphaty (empathy), and interest in quality control and costs. Material participants acted well duringthe implementation of community service